2023
DOI: 10.20944/preprints202303.0026.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Industrial Transfer Learning for Multivariate Time Series Segmentation: A Case Study on Hydraulic Pump Testing Cycles

Abstract: Industrial data scarcity is one of the largest factors holding back the widespread use of machine learning in manufacturing. To overcome this problem, the concept of transfer learning was developed and it achieved high attention in recent industrial research. Our paper focuses on the problem of time series segmentation and presents the first in-depth research about transfer learning for deep-learning based time series segmentation on the example of industrial end-of-line pump testing. In particularly, we inves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Almost none of the previous works in the TL field focused on the task of TSS. While TSS problems might be less prevalent in the everyday life of companies and researchers, they still deserve attention due to their importance for fields like human action recognition [ 26 ], sleep staging [ 5 ], and operational state detection [ 6 ]. One contribution had a first look at the topic [ 9 ] and successfully showed that feature extraction process of a TSS–CNN model can be improved when pretraining the model with a large, domain-independent source dataset .…”
Section: Literature Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost none of the previous works in the TL field focused on the task of TSS. While TSS problems might be less prevalent in the everyday life of companies and researchers, they still deserve attention due to their importance for fields like human action recognition [ 26 ], sleep staging [ 5 ], and operational state detection [ 6 ]. One contribution had a first look at the topic [ 9 ] and successfully showed that feature extraction process of a TSS–CNN model can be improved when pretraining the model with a large, domain-independent source dataset .…”
Section: Literature Researchmentioning
confidence: 99%
“…There is a lack of research on TL strategies for TSS in general, and even more so for TSS use cases in industrial settings. The pump testing dataset we use in this paper was published in the context of one of our previous works [ 6 ]. In that work, the dataset was used for TSS experiments in which the availability of a sufficient amount of training data was ensured.…”
Section: Literature Researchmentioning
confidence: 99%
See 3 more Smart Citations